A New Forest-Dwelling Frog Species of the Genus Adenomera (Leptodactylidae) from Northwestern Brazilian Amazonia - De Carvalho, Thiago R. [UNESP]; Simões, Pedro I.; Gagliardi-Urrutia, Giussepe; Rojas-Runjaic, Fernando J. M.; Haddad, Célio F. B. [UNESP]; Castroviejo-Fisher, Santiago (American Society of Ichthyologists and Herpetologists (ASIH), 2020)
We describe a new species of the South American frog genus Adenomera, based on external morphology, color patterns, advertisement call, and mtDNA sequences. The new species was collected from the Japurá River basin in northwestern Brazilian Amazonia and is distinguished from all congeners by the combination of large snout-vent length (SVL), toe tips unexpanded, presence of antebrachial tubercle on underside of forearm, and by a multi-note advertisement call composed of non-pulsed notes. This new species is part of the A. lutzi clade together with a candidate new species known as Adenomera sp. P and A. lutzi. The three species have the largest SVL in the genus. The presence of toe tips fully expanded and a single-note advertisement call distinguish A. lutzi from the new species. Acoustic and morphological data are still required to assess the taxonomic identity of Adenomera sp. P. Our new species of Adenomera is the third anuran species described from the Solimões-Japurá interfluve. This flags this poorly known region of lowland forests as an important area of species richness in northwestern Amazonia.